2018
DOI: 10.21839/jfna.2018.v1i1.216
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rearing system and cooking method on the carnosine and anserine content of poultry and game meat

Abstract: Poultry meat has been shown to be a rich source of carnosine and anserine (CRC) but little is known of the effects of bird species and the system under which it is reared have on the concentrations of CRC. Retail samples of breast meat from conventional chicken, free range chicken and pheasant, and breast meat from wild caught pheasant were procured and subjected to five different cooking methods: frying, grilling, boiling, microwaving and roasting. CRC were greater in uncooked pheasant than chicken (P< 0.05) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…The anserine contents of BCF and BAF significantly decreased throughout storage; however, the anserine content of BAF was higher than that of BCF ( P < 0.001) on all days. Juniper and Rymer (2018) reported that the anserine contents were significantly higher in free-range chicken breast meat than in conventional chicken breast meat. These authors reported that the increase in anserine contents may be due to a higher amount of exercise in the free-range chickens.…”
Section: Resultsmentioning
confidence: 98%
“…The anserine contents of BCF and BAF significantly decreased throughout storage; however, the anserine content of BAF was higher than that of BCF ( P < 0.001) on all days. Juniper and Rymer (2018) reported that the anserine contents were significantly higher in free-range chicken breast meat than in conventional chicken breast meat. These authors reported that the increase in anserine contents may be due to a higher amount of exercise in the free-range chickens.…”
Section: Resultsmentioning
confidence: 98%
“…This was consistent with the ratio range reported in the literature, that is, the ratio of chicken Car to Ans was between 0.28 and 0.81. [19] The Car and Ans in meat could be leached into boiling water because of their high water-solubility, which might be the reason for the high content of Car and Ans in five kinds of chicken soup samples. Meanwhile, the TAVs of Ans were all greater than 1 (Table 3) in chicken soup samples, except for CSS samples, which indicated that it was important contributor to chicken soup taste.…”
Section: Small Peptidementioning
confidence: 99%
“… Juniper and Rymer (2018) reported that the increase in anserine level in breast meat may have been contributed by the higher amount of exercise when broilers were reared in the free-range system providing more space to move. Anserine in the breast meat was not significant but tends to increase in broilers reared in AF providing more space allowing more physical activity than that in CF.…”
Section: Resultsmentioning
confidence: 99%